Democratic governance and the social condition in the Anglophone Caribbean - Ryan, Selwyn (ISER. UWI St. AugustineTT, 1996)
Focuses on aspects such as size and good governance; spoils system and governance; structural adjustment and good government; parliamentary accountability and control; corruption, drug trafficking and governance; poverty and good governance; whither good governance in the Caribbbean; and enhancing the social environment that sustains good governance.